Assessment of Human Capital in the Agricultural Enterprises of the Republic of Kazakhstan - Bulkhairova, Zhanna Serikovna; Alenova, Karlygash Toleubaevna; Nukesheva, Anar Zhaskaratovna; Ismailova, Aliya Sabirzhanovna (International Journal of Economics and Financial Issues, 2016)
Nowadays for Kazakhstani agricultural enterprises that work in the present conditions the most important is the formation of new and more effective control systems, where the main thing is the correct assessment and subsequent management of human capital. The author assesses the human capital in agriculture in the Republic of Kazakhstan. To assess the level of development of human capital in agriculture, two interconnected blocks of indicators: indicators of conditions of the human capital and indicators of its operation results have been selected. The authors performed quantitative transfer of characteristic values into their qualitative analogues, did the ranking of areas based on entropy and analyzed by the method of factor analysis the dynamics of human capital development in agriculture. Keywords: Human capital, human capital assessment, production indicators, financial indicators, social indicators, innovation, entrepreneurship indicators JEL Classifications: J24, J43, J50, Q12, O15